Real-time RT-PCR assays for discriminating influenza B virus Yamagata and Victoria lineages - Nakauchi, Mina; Takayama, Ikuyo; Takahashi, Hitoshi; Oba, Kunihiro; Kubo, Hideyuki; Kaida, Atsushi; Tashiro, Masato; Kageyama, Tsutomu (Journal of virological methods, 2014)
•We developed one step real-time RT-PCR assays to discriminate two lineages of influenza B viruses.•The developed assays were evaluated using in vitro transcribed control RNA, clinical specimens, and clinical isolates.•The assays were shown to have high sensitivity and high specificity.•The results from the assays were consistent with those from a hemagglutination inhibition (HI) test, which is a standard method to define the lineage of influenza B virus.•The developed assays will be useful for the diagnosis and surveillance of influenza B viruses. Since the late 1980s, two genetically and antigenically distinct lineages of influenza B virus, namely, B/Victoria/2/87-like (B/Victoria) and B/Yamagata/16/88-like (B/Yamagata), have co-circulated. In this study, one-step real-time reverse transcription-PCR (rRT-PCR) assays were developed to differentiate B/Victoria and B/Yamagata lineages. The assays were evaluated using in vitro transcribed control RNA, isolated viruses, and other respiratory pathogenic viruses, and were shown to have high sensitivity, good linearity (R2=0.99), and high specificity. Using the developed rRT-PCR assays, 169 clinical specimens collected between 2010 and 2013 were then tested, resulting in the identification of 20 clinical specimens as positive for influenza B virus. Of these, 14 and 6 samples were identified as positive for the B/Victoria and B/Yamagata lineages, respectively, whereas 149 samples were negative for the influenza B virus. The rRT-PCR assays were also examined using 20 clinical isolates from 20 influenza B virus-positive specimens, revealing that there was no discrepancy between the results from the rRT-PCR assays and the hemagglutination inhibition (HI) test, with the exception that one clinical isolate with different antigenicity could not be discriminated by the HI test. The present results suggest that these highly sensitive and specific assays are useful not only for diagnosing influenza viruses but also for their surveillance.